1998
DOI: 10.1007/s004240050572
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term changes in medullary osmolality on heat shock proteins HSp25, hsp60, HSP72 and HSP73 in the rat kidney

Abstract: The influence of diuresis and antidiuresis on the expression of heat shock proteins (HSP) 25, 60, 72 and 73 in the renal cortex and outer and inner medulla of Wistar rats was analysed. Medullary osmolality was reduced by long-term diuresis (3% sucrose in the drinking water for 3 weeks) and subsequently enhanced by transition to a concentrating state by giving normal drinking water again in combination with deamino-D-arginine vasopressin (dDAVP) for 5 days. Western blot analyses revealed that neither HSP73 nor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 41 publications
0
37
0
Order By: Relevance
“…Changes in the osmolality of the renal medulla resulting from water loading (20), diuretics (28), dehydration (25), and drinking salty water (9) have been reported in the literature. Drinking 1% NaCl in water for 7 days has been reported to increase the medullary osmolality in rats (9); however, the effect of high-salt diet on medullary Na ϩ concentration is not yet totally clear.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the osmolality of the renal medulla resulting from water loading (20), diuretics (28), dehydration (25), and drinking salty water (9) have been reported in the literature. Drinking 1% NaCl in water for 7 days has been reported to increase the medullary osmolality in rats (9); however, the effect of high-salt diet on medullary Na ϩ concentration is not yet totally clear.…”
Section: Discussionmentioning
confidence: 99%
“…They reside at serine residues (Ser78 and Ser82) occurring in RXXS motifs that are known to be recognized by ribosomal protein S6 kinase II [33]. Phosphorylation can also be modulated by factors such as cholecystokinin [34], 12-O-tetradecanoylphorbol-13-acetate, tumor necrosis factor-alpha (TNF-alpha) [35], changes in osmolality [36], in Ca 2+ concentration [37], follicle stimulating hormone [38], cyclosporine [39], and heavy metals like cadmium or vanadium [40,41]. Since numerous isoforms are isolated by 2-DE in human myocardial tissue, phosphorylation may not be the only posttranslational modification [42] that occurs in hsp27 response to various inducible stimuli.…”
Section: Molecular Structurementioning
confidence: 99%
“…This finding suggests that this rise in HSP72 expression is probably not due to specific effects of potassium but Cell Physiol Biochem 2000; 10:303-306 rather to an increase in extracellular tonicity. The observation that several medullary stress factors act synergistically on HSP72 expression suggests that the relatively high content of HSP72 in the inner medulla of chronically diuretic rats [13] is due to the concerted action of several, albeit weakly acting, stressors.…”
mentioning
confidence: 99%
“…These investigations showed that in kidneys producing a concentrated urine HSP25, αB crystallin, HSP72 and OSP94 display a distribution pattern corresponding to that of tissue solute concentrations: high, intermediate and low contents of these HSPs in inner medulla, outer medulla and cortex, respectively. This distribution pattern, however, is not observed for other members of the HSP family, such as the constitutively expressed HSP73 (also termed HSC70) and HSP60 [11,13]. In addition, the expression of HSP25 mRNA [14], HSP72 [8,13], and OSP94 mRNA [10] changes appropriately with the diuretic state.…”
mentioning
confidence: 99%
See 1 more Smart Citation